Urban Experience And Design, (Org.) by Justin B. Hollander and Ann Sussman, Book Review - Neves , Pedro Soares (Architecture Image Studies, 2021)
This collection of articles, turned into chapters, shows of great significance for the contribution of knowledge about the connection between User Urban Experience and our built environment. In the interception of architecture, planning, design and psychology. Although not specifically in line with the User Experience (UX) writings that blends borders between digital and physical world (such as the works of Don Norman), this book talks about the use of specific technologies and biological interpretations. In some chapters Biometric eye tracking and terms as fixation, saccade and pre-attentive processing will be the foundation for collecting data on urban conditions that respond to innate human needs. We can find insights from neuroscience such as the fact that most of our brains work, happens without any conscious awareness of control (11 billions bits of information from the body per second, conscious brain handle 50 of this bits per second (Mlodinow, L., 2013). Subliminal: How your unconscious mind rules your behaviour. New York: Vintage.) Using eye tracking to create buildings people easily take in is proposed, giving an example how art can perhaps create a positive of urban experience. Face bias, and the relevance of façade, as mammals looking at faces make us feel safe and at our best. We as social species look for relationships all the time (Porges, S. W. (2017). The pocket guide to the polyvagal theory: The transformative power of feeling safe. New York: Norton.).